Persuasive Missionary Endeavor in The Story of Prophet Musa and Fir’aun: Study of Chapter Thaha Verse 44 - Fauziah, Mira (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Persuasive da'wah is a da'wah that is carried out in a gentle and warm way. Not all da'i can apply persuasive da'wah to their mad'unya. Some da'i still exist who preach using language that does not touch the heart. This paper aims to find out how persuasive preaching was carried out by the prophets Moses and Aaron against Fir'aun. This paper uses the countenance analysis method, which analyzes the meaning of Surah Thaha, verse 44, of the Qur'an using the theory of persuasive da'wah. The results showed that the Al-Quran Surah Thaha, verse 44, reveals the story of Prophet Moses and Prophet Aaron preaching to Pharaoh in a gentle way even though Pharaoh knew that he was a despotic king and disobeyed Allah. The term "qaulan layyina" has a meaning that is gentle, pleasant to hear, touches the heart, and reassures the mind. Prophet Moses and Prophet Aaron have done persuasive da'wah with several methods, namely: the association method, integration, payoff, fear-arousing, and icing methods. This was done in the hope that Pharaoh would be touched by his heart and fear Allah so that he would believe in